2014
DOI: 10.1016/j.ecoenv.2014.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Basal and benzo[a]pyrene-induced expression profile of phase I and II enzymes and ABC transporter mRNA in the early life stage of Chinese rare minnows (Gobiocypris rarus)

Abstract: a b s t r a c t ATP-binding cassette (ABC) transporters together with phase I and II detoxification enzymes have been considered as included in a cellular detoxification system. Previous studies have highlighted the involvement of aryl hydrocarbon receptor (AHR) and Cyp1a in PAH-induced embryo toxicity. However, the response of other xenobiotic enzymes/transporters in PAH-mediated embryo toxicity is not fully characterized. In the present study, rare minnow embryos were exposed to 10 and 100 mg/L BaP within 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Unfortunately, there are only a few available studies on the role of ABCC in PAHs detoxification in mollusks for establishing comparisons. In the present study, a significant induction of McoABCC was also observed, suggesting that it possibly takes part in Bap scavenging, as ABCB1 does (Costa et al, 2012;Yuan et al, 2014;Kim et al, 2017). Notably, in 100 µg/L Bap group, the mRNA expression levels of McoABCB1 and McoABCC were significantly induced at 1 dpe, sharply decreased over time, and ultimately reached a lower level compared to control group.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Unfortunately, there are only a few available studies on the role of ABCC in PAHs detoxification in mollusks for establishing comparisons. In the present study, a significant induction of McoABCC was also observed, suggesting that it possibly takes part in Bap scavenging, as ABCB1 does (Costa et al, 2012;Yuan et al, 2014;Kim et al, 2017). Notably, in 100 µg/L Bap group, the mRNA expression levels of McoABCB1 and McoABCC were significantly induced at 1 dpe, sharply decreased over time, and ultimately reached a lower level compared to control group.…”
Section: Discussionsupporting
confidence: 63%
“…However, the mRNA levels of ABCB1b and ABCC1 were not significantly changed after exposed to a BAP-containing diet and water (Costa et al, 2012). In the fish Gobiocypris rarus, Bap significantly induced the transcriptional expression levels of three ABC transporters (i.e., ABCC1, ABCC2, and ABCG2) in a dosedependent manner, while demonstrated no apparent effect on ABCB1 mRNA expression (Yuan et al, 2014). Collectively, ABC transporters have a highly complex detoxifying response to Bap exposure, and the available data are still confusing, especially in mollusks, where the relevant information is very scarce and requires further investigation.…”
Section: Introductionmentioning
confidence: 88%
“…These defense systems are modulated by phase detoxification enzymes such as GSTs, SULTs, uridine 5 -diphospho-glucuronosyltransferases (UGTs), and ABCCs that induce the excretion of toxicants through urine [58]. Previous studies showed that B[a]P-induced genotoxicity was reduced by the modulation of phase detoxifying enzymes before BPDE-DNA adduct formation [17,47]. GSTs are typical phase II detoxifying enzymes and are important in reducing B[a]P-induced DNA damage by inhibiting the formation of DNA adducts and 8-oxo-G [59].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 and PXR are well-known as inducers of phase II detoxification enzyme and phase III transporter expression [17,33,[38][39][40]. To elucidate the pathways involved in the silymarin-mediated suppression of BPDE metabolites, the effects of Nrf2 and PXR translocation were evaluated using immunofluorescence staining.…”
Section: Stimulation Of Nuclear Translocation Of Nrf2 and Pxr By Silymentioning
confidence: 99%
See 1 more Smart Citation